Estudo preliminar da separação supersônica do gás natural utilizando CFD - Pettinatti, Jéssica Lincoln (Universidade Federal de São Carlos, 2022)
Brazil's natural gas reserve amounts to approximately 0.4 trillion cubic meters. It is one of the biggest in volume in the American Continent. Its extraction in Brazilian territory is concentrated in the Pre-Salt area, an 800-kilometer stretch that stretches from the northern coast of Santa Catarina to the state of Espirito Santo, with the Campos sedimentary basin in Rio de Janeiro standing out. Undoubtedly, along with the high production capacity, one can also highlight the environmental gains from using natural gas, since the capacity for CO2 emissions is much lower than that of fossil fuels, thus being considered a very attractive energy alternative. However, the CO2 present in the composition of natural gas, along with water and other contaminants, is considered a problem when it comes to the quality of the final product, and should be separated from the product of interest and destined for environmentally and commercially appropriate purposes. To this end, several techniques are currently being used to purify natural gas, such as adsorption, absorption, and molecular sieves. More recently, the potential has been identified to use supersonic technology for bulk removal of pollutants from natural gas. The operation of the supersonic separator is composed of expansion processes, cyclonic gas-liquid separation, and re-compression of the natural gas. First, the gas temperature is dropped by up to 50°C through adiabatic cooling along the inlet nozzle to expand the gas until supersonic velocities are reached. Consequently, water and hydrocarbon droplets are condensed, which are separated from the rest of the bulk by centrifugation in the cyclonic region of the separator. Despite being a very attractive alternative for the separation of CO2, the supersonic separation presents highly complex and turbulent flows, with the presence of high vorticity, which makes its study by conventional methods difficult. Thus, the present work aimed to perform a preliminary investigation of the flow in supersonic separators through CFD analysis using the Simcenter STAR-CCM+ software. From the analysis of two different baffle geometries, it was possible to investigate the direct influence of particle diameter on the efficiency of natural gas separation. For particle diameters of 2 µm, efficiency higher than 50% was obtained, while for diameters smaller than 0.8 µm, efficiency was lower than 40%. Deflector 1 had the highest efficiency values, but deflector 2 had the lowest pressure drop values.
Preliminary study of supesonic separation of natural gas using CFD
Keywords: Gás natural; Separador supersônico; CFD; Multifásico; Natural gas; Supersonic separator; Multiphase; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA